Deformation twinning-induced dynamic recrystallization during laser powder bed fusion. (15th January 2022) - Sabzi, Hossein Eskandari; Li, Xiao-Hui; Zhang, Chi; Fu, Hanwei; San-Martín, David; Rivera-Díaz-del-Castillo, Pedro E.J.
Graphical abstract: Abstract: Nanotwin formation is observed during laser powder bed fusion (LPBF) of austenitic stainless steels fabricated with various process parameters. Transmission electron microscopy was employed to reveal the nature of such twins, which are formed due to the high strain rapid solidification inherent to LPBF. Dynamic recrystallization (DRX) was also activated during LPBF, and induced by the deformation nanotwins. A thermostatistical model is proposed to determine the critical conditions for twinning-induced DRX; the model is validated with the reported experimental results. This modelling approach offers a method to microstructurally engineer austenitic stainless steels for potential applications needing high strength and ductility.